TMOD-41. ORTHOTOPIC PATIENT-DERIVED XENOGRAFT MODELS OF BRAIN METASTASIS: PLATFORMS FOR PRECISION ONCOLOGY AND UNDERSTANDING TUMOR BIOLOGY. (11th November 2019) - Dankner, Matthew; Savage, Paul; Rose, April; Lajoie, Mathieu; Diaz, Roberto; Park, Morag; Watson, Ian; Guiot, Marie-Christine; Petrecca, Kevin; Siegel, Peter
Abstract: RATIONALE: Brain metastasis (BrM) occurs in 10–20% of cancer patients and results in median survival times of less than 1 year. In order to accurately develop novel treatment strategies, there is an urgent need to establish animal models of BrM that resemble the human disease. OBJECTIVES: We sought to establish orthotopic patient-derived xenografts (PDX) models of BrM from diverse solid cancers to understand biological characteristics of BrM and to test novel drug candidates in their ability to treat BrM. METHODS: 35 PDXs were established by subcutaneous or mammary fat pad implantation and by intracranial injection. PDXs were validated by immunohistochemistry of routine pathological markers in patient specimens and matched primary and intracranial PDXs. PDXs were applied for precision medicine in class II BRAF mutant tumours treated with targeted therapy and in the pre-clinical development of a novel therapeutic agent, DZ-2384, which may have applications in treating BrM. They were also used to understand the underlying biology of leptomeningeal dissemination from parenchymal BrM. RESULTS: PDXs reveal strong similarity to patient specimens by IHC staining. Class II BRAF mutant PDXs are optimally sensitive to BRAF and MEK inhibitors compared to either agent alone. DZ-2384 is effective in slowing the progression of breast cancer BrM. PDXs that most efficiently invade the leptomeninges display loss of E-Cadherin expression, suggesting the role of an epithelial-mesenchymal transition in this process. CONCLUSIONS: PDXs of BrM represent important models that can be employed to test novel therapeutics and to improve understanding of molecular mechanisms engaged by BrM.